Programming web applications with node, express and pug - Krause, Jorg (Apress, 2017)
This book teaches you how to program modern web applications using the full Node.js platform, including Node.js on the server, Express for middleware and routing, and Pug (formerly Jade) to simplify the creation of views. Node.js is the foundation of all full JavaScript apps and plenty of books cover its full usage. This book focuses on how to use it to create server-based, modern web applications. Using Node.js alongside Express and Pug - the brand new version of Jade - you can create modern web applications solely using JavaScript. This book teaches you how to structure and build your app from scratch, and make development easy.